Aprovechamiento del gas natural para la reducción del dióxido de carbono producido en el proceso industrial del recobro mejorado térmico por medio del solar EOR (2017)
The following monograph had the general objective of establishing the reduction of carbon dioxide through the use of the solar EOR technique, which allows alternatives for the use of natural gas. This was done by means of a definition of the industrial process, this was covered from its preliminary phase showing each of the solar panels that can be used in this technique, in order to understand how the replacement of natural gas is generated as an energy source for the generation of value, this will give the process a total reduction in the emission of greenhouse gases, especially CO2, which favors the company to generate recognition and status by being friendly to the environment and will generate a better use of gas natural, which can be exported as liquefied natural gas, used in industrial processes with energy deficit or to supply self-sufficiency problems that the country has.